Teachers’ efficacy in teaching physical education in primary schools in the Motheo District, Free State Province of South Africa - Muomezie, Sandra Ijeamaka ([Bloemfontein] : Central University of Technology, Free State, 2018)
Physical Education (PE) is the only school subject that is define through physical activity. Participating in physical activity provides the learners with the opportunity to develop their motor skills and cultivate the habit of living a healthy life style throughout their life. However, PE has been marginalised both globally and in South Africa. The situation of PE in South Africa is complicated, that is, PE during the apartheid regime (before 1994) was a non-examination subject. With the inception of democracy, PE lost its status as an independent subject as it became a module in Life skill learning area. The objective of this study was to investigate teachers’ efficacy (confidence) in teaching Physical Education in primary schools in the Motheo district and to suggest valuable solutions to the problem. Four questions were raised to achieve the objectives of the study. To answer these basic research questions, a descriptive survey research method was employed. Fifty two (52) primary schools and one hundred and four (104) teachers were the participants of the study. The schools were selected by simple random sampling, and the teachers selected through a purposive sampling method. Out of the one hundred and four (104) questionnaires that were distributed in person by the researcher, only eighty six (86) copies were filled in and returned. After the analysis of the collected data, the following findings were made: the teachers teaching the PE module in Life Skills in the primary schools in the Motheo district were not qualified to teach it; that the teachers are not PE specialists and do not have a PE specialist in their school; that teachers are not meeting the required time for teaching PE which according to the European Commission (EC) (2015:12) is five lessons per week (5 hours); there is a lack of facilities and equipment; that teachers are not provided with In- Service Training (INSET) training; that teachers have very low efficacy in teaching some PE content areas such as athletics, dance, swimming, gymnastics, adapted PE. Other factors affecting teachers in teaching PE in primary schools in the Motheo district are educational background and knowledge factors, class size and time allotment factors, PE situation in Life Skills factors, and physical resources factors. For further improvement, PE teachers are assigned with the responsibility of conducting different PE activities. They should, therefore, be equipped with the necessary knowledge as well as skills to teach this module effectively. PE teachers should be provided with in-service training, assistance and the supervision of a PE specialist, conducive and standard PE facilities and equipment, and the time allocation for PE on the school timetable should be improved. The Department of Education (DoE) should make it possible for the teachers to take active part in the curriculum development so that they can provide their input concerning the teaching of PE in school. The DoE should address the problems of teaching PE as a part of Life Skills, but as an integrated whole.
Thesis (Master of Education) -- Central University of Technology, Free State, 2018
Keywords: Central University of Technology, Free State -- Dissertations; Physical Education